Re-treatment with etanercept is as effective as the initial firstline treatment in patients with juvenile idiopathic arthritis - Jens Klotsche (Arthritis Research & Therapy, 2021)
Abstract Objectives To determine (i) correlates for etanercept (ETA) discontinuation after achieving an inactive disease and for the subsequent risk of flare and (ii) to analyze the effectiveness of ETA in the re-treatment after a disease flare. Methods Data from two ongoing prospective registries, BiKeR and JuMBO, were used for the analysis. Both registries provide individual trajectories of clinical data and outcomes from childhood to adulthood in juvenile idiopathic arthritis (JIA) patients treated with biologic disease-modifying anti-rheumatic drugs (bDMARDs) and conventional synthetic DMARDs (csDMARDs). Results A total of 1724 patients were treated first with ETA treatment course (338 with second, 54 with third ETA course). Similar rates of discontinuation due to ineffectiveness and adverse events could be observed for the first (19.4%/6.2%), second (18.6%/5.9%), and third (14.8%/5.6%) ETA course. A total of 332 patients (+/−methotrexate, 19.3%) discontinued ETA after achieving remission with the first ETA course. Younger age (hazard ratio (HR) 1.08, p < 0.001), persistent oligoarthritis (HR 1.89, p = 0.004), and shorter duration between JIA onset and ETA start (HR 1.10, p < 0.001), as well as good response to therapy within the first 6 months of treatment (HR 1.11, p < 0.001) significantly correlated to discontinuation with inactive disease. Reoccurrence of active disease was reported for 77% of patients with mean time to flare of 12.1 months. We could not identify any factor correlating to flare risk. The majority of patients were re-treated with ETA (n = 117 of 161; 72.7%) after the flare. One in five patients (n = 23, 19.7%) discontinued ETA again after achieving an inactive disease and about 70% of the patients achieved an inactive disease 12 months after restarting ETA. Conclusion The study confirms the effectiveness of ETA even for re-treatment of patients with JIA. Our data highlight the association of an early bDMARD treatment with a higher rate of inactive disease indicating a window of opportunity.